PENURUNAN KADAR SIANIDA DALAM LIMBAH CAIR TAPIOKA MENGGUNAKAN FOTOKATALIS TiO2 - Kapti Riyani; Tien Setyaningtyas (Molekul, 2010)
Cyanide compound is one of the organic material contained in wastewater of tapioca production, which is a highly toxic substance for life. According to the results of physical and chemical properties of liquid waste samples of tapioca starch in the deposition process in the industry taken from Pancasan Village, Ajibarang, Banyumas, cyanide concentration in the effluent was 3.8 mg/L while the maximum level of cyanide allowed in industrial wastewater are 0.5 mg/L. Therefore, a method to reduce the concentration of cyanide is needed. One of the method is using of TiO2 catalyst. This study was aimed to determine the effect of the pH and UV irradiation time on photocatalytic activity of TiO2 to reduce the levels of cyanide on tapioca wastewater from PT. HARUM BUNGA, Purbalingga.This study uses a thin layer of TiO2 photocatalyst prepared by suspension of TiO2 coating on the glass plate that was dried at 120ºC and conducted with variations of pH that were 2, 5, 7, 8, 9, 10, and 13 in the wastewater to determine the optimum pH, continued by time variation of UV radiation for 1, 2, 4, 6, 8, 10, and 12 hours. The results showed that the largest percentage decrease in the concentration of cyanide occurs at pH 9 that is equal to 88.6361% and the largest percentage decrease in the concentration of cyanide by irradiation with UV light occurs after 10 hours irradiation, up to 93.7929%.